Pemanfaatan Internet Sehat, Bertanggungjawab dalam Pemasaran Desa Wisata Way Tebing Cepa - Dewi Silvia; Nur Salma; Mohammad Renandi Ekatama; Helmita Helmita; Resy Anggun Sari; Novalita Novalita; Armalia Reny WA (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Internet media with its offers, choice of various sites and freedom of access is like a double-edged sword, on the one hand it can have a positive impact and on the other hand it can have a negative impact. To avoid crime in cyberspace, we always emphasize the basic principles that must be known when using the internet. Basic principles in the real world also apply in the virtual world. Healthy and safe use of the internet needs to be instilled from an early age through learning healthy internet ethics. This needs to be conveyed to avoid bad habits in the real world being carried over into the virtual world and causing negative effects in the real world. This service activity carried out by lecturers from Indonesian partner universities carries the theme "Healthy and Responsible Use of the Internet in Marketing Way Tebing Cepa Tourism (WTC) Kalianda, South Lampung Regency" where the aim of this activity is to provide knowledge to Way Tebing Cepa tourism managers in using the internet both in promotions and otherwise in order to avoid unhealthy and irresponsible internet use.